Novel approaches to antifungal therapy. Issue 2 (8th January 2018) - Thompson, George R.; Patterson, Thomas F.
Abstract : Novel use of inhaled antifungal therapy is of interest to minimize systemic toxicity and drug–drug interactions while improving drug delivery directly to the site of infection. See the case report from Solé et al on page 504 .